Keragaman genetik Gonystylus bancanus (miq.) kurz berdasarkan penanda RAPD (Random Amplified polymorphic DNA) - Antonius WPBC Widyatmoko; nfn Aprianto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2013)
Gonystylus bancanus (Ramin) is one of the most valuable timber species in peat swamp forest. Over harvesting and illegal logging had decreased the potential of the species. Thus, conservation of the species becomes a very crucial activity to be carried out. In order to conserve efficient and effectively, it is important to gather information of genetic diversity and its distribution, and also genetic relationship among populations. In this activity, 86 loci from 20 RAPD primers were used for analyzing genetic diversity of 10 populations of ramin distributed in Kalimantan and Sumatera. As a result, mean genetic diversity of the 10 populations was 0.329, and mean genetic distance between populations was 0.061. Genetic diversity within population (94%) was higher than between populations (6%). Based on cluster analysis, 10 populations of ramin were divided into 2 groups. The first group was consisted of Kuok B, and the remaining 9 populations were clustered into the second group. The second group could be divided into 3 sub-groups, the first sub-group consisted of Mesukuh I, Mesukuh II, Pakilat I, Kanarakan dan Nyaru Menteng, second sub-group was consisted of Pakilat II, and the third sub-group was consisted of PT Diamond, Kuok A and Berbak.